2020
DOI: 10.3390/nu12092619
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits and Their Relationship to Oral Health

Abstract: The objective of this research was to compare the healthy behaviors and caries index of young people in school to obtain an overview of their lifestyles, which would enable the development of educational programs for the promotion of oral health. The study design was carried out using a descriptive, cross-sectional, and observational methodology with a mixed approach. 380 twelve-year-old students participated in this research conducted in the city of Riobamba-Ecuador. The techniques used were observational and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…The current findings indicate that a causal role of vitamin C as an isolated micronutrient on dental caries and periodontitis is unlikely. Although previous observational studies have found that higher consumption of fruits and vegetables rich in vitamin C may prevent periodontal disease progression (Skoczek‐Rubińska et al, 2018; Tenelanda‐López et al, 2020), it is more likely that a synergetic effect of various constituents such as minerals, numerous phytochemicals, and dietary fibre in fruits and vegetables rather than vitamin C alone contributed to those inverse associations. Moreover, another most likely reason for such associations in these observational studies is residual confounding: that is, participants with a healthy lifestyle are more likely to increase the consumption of fruits and vegetables as well as oral hygiene protection or anti‐caries behaviour.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The current findings indicate that a causal role of vitamin C as an isolated micronutrient on dental caries and periodontitis is unlikely. Although previous observational studies have found that higher consumption of fruits and vegetables rich in vitamin C may prevent periodontal disease progression (Skoczek‐Rubińska et al, 2018; Tenelanda‐López et al, 2020), it is more likely that a synergetic effect of various constituents such as minerals, numerous phytochemicals, and dietary fibre in fruits and vegetables rather than vitamin C alone contributed to those inverse associations. Moreover, another most likely reason for such associations in these observational studies is residual confounding: that is, participants with a healthy lifestyle are more likely to increase the consumption of fruits and vegetables as well as oral hygiene protection or anti‐caries behaviour.…”
Section: Discussionmentioning
confidence: 94%
“…Tenelanda-L opez et al, 2020), it is more likely that a synergetic effect of various constituents such as minerals, numerous phytochemicals, and dietary fibre in fruits and vegetables rather than vitamin C alone contributed to those inverse associations. Moreover, another most likely reason for such associations in these observational studies is residual confounding: that is, participants with a healthy lifestyle are more likely to increase the consumption of fruits and vegetables as well as oral hygiene protection or anti-caries behaviour.…”
mentioning
confidence: 99%
“…The BDHQ asks about the consumption frequency of selected foods to estimate the dietary intake of fifty-eight food and beverage items during the preceding month. Details of the BDHQ's structure, method of calculating dietary intake are described by its developers [16][17][18][19][20]. Calculation of nutritional intakes was ordered from the DHQ support center (Gender Medical Research, Co. Ltd., Tokyo, Japan).…”
Section: Brief-type Self-administered Diet History Questionnaire (Bdhq)mentioning
confidence: 99%
“…Inverse associations were found between fatty acids, vitamin C, vitamin E, beta-carotene, fiber, calcium, dairy, fruits, and vegetables and risk of periodontal disease [17]. The relationship between oral health and nutrition is primarily related to masticatory function, but it is complicated by other factors such as race, culture, lifestyle, and personal preferences [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Other kinds of cariogenic bacteria adsorb on the surface of the membrane to form dental plaque, which is also the first step in the formation of dental caries (7). In addition, poor oral hygiene habits, education, living standards, and orthodontics may also be risk factors for caries (8,9). A longitudinal cohort study by Warren et al (10) found that educational attainment, brushing frequency, household water fluoride concentrations, and 100% juice consumption were associated with the high incidence of dental caries in adolescents and the influence of the mother on the adolescent.…”
Section: Introductionmentioning
confidence: 99%